RADIO-GUIDED PARATHYROIDECTOMY USING Tc-99m MIBI FOR ECTOPIC PARATHYROID ADENOMA : A CASE REPORT - Jankulovska, Anamarija; Yentur, Zeynep; Borg, Ylenia; Ozmenekse, Ege; Stojkovska, Natasha; Manevska, Nevena; Stojanoski, Sinisha (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Ectopic parathyroid adenomas pose diagnostic and therapeutic challenges. Preoperative Tc-99m sestamibi SPECT/CT scan and radio-guided surgical technique enhance intraoperative accuracy enabling precise detection of an ectopic parathyroid gland.  Case presentation: We present a case of a 54-year-old female patient with PHPT due to an ectopic parathyroid adenoma located in the suprasternal region. Neck ultrasonography showed a normal-sized thyroid with a cystic nodule in the right lobe and a hypoechoic mass in the suprasternal region, raising suspicion of an enlarged parathyroid gland. Dual-phase SPECT parathyroid scintigraphy with Tc-99m sestamibi revealed homogeneous uptake in both thyroid lobes and intense accumulation below the right thyroid lobe, suggesting hyperfunctional ectopic parathyroid tissue. The patient successfully underwent a minimally invasive radio-guided parathyroidectomy using a handheld gamma probe.  Conclusion: The management of ectopic parathyroid adenomas requires a multidisciplinary approach, utilizing advanced imaging and minimally invasive techniques such as parathyroid scintigraphy with SPECT/CT and intraoperative gamma probes for the safe and precise removal of these hyperfunctional glands. Keywords:   Ectopic parathyroid adenoma, 99mTc-sestamibi scintigraphy,SPECT/CT, radio–guided surgery.